Deep brain stimulation as treatment for dystonic storm in pantothenate kinase-associated neurodegeneration syndrome: case report of a patient with homozygous C.628 2 T > G mutation of the PANK2 gene - DAĞÇINAR, ADNAN; GÜNAL, DİLEK; TÜRKDOĞAN, DİLŞAD; BAYRAKLI, FATİH; BAYRİ, YAŞAR (SPRINGER WIEN, 2015)
Pantothenate kinase-associated neurodegeneration (PKAN) syndrome is an autosomal-recessive neurodegenerative disease that causes progressive generalized dystonia. Currently, the disorder remains pharmacologically intractable. Herein we report the first case in which deep brain stimulation helped to relieve dystonic storm in a patient with PKAN syndrome who had homozygous c.628 2 T > G mutation of the PANK2 gene. A 10-year-old boy with PKAN disease presented with dystonic storm and was admitted to the emergency department. Examination revealed generalized dystonia and impaired breathing due to involvement of the respiratory muscles. The patient underwent surgery for bilateral globus pallidus internus deep brain stimulation. The patient showed marked response to treatment.
Keywords: Deep brain stimulation; Globus pallidus internus; Dystonia; PKAN; c.628 2 T>G mutation; PANK 2 gene; HALLERVORDEN-SPATZ-SYNDROME; PALLIDAL STIMULATION; GLOBUS-PALLIDUS; DISEASE